Alex Rider - Stormbreaker: A Graphic Novel Experience in a German EFL Classroom - Svenja Brinkmann (CLELEjournal, 2015)
This article gives an insight into the use of the graphic novel Alex Rider - Stormbreaker (Horwitz, 2006) in a German secondary school (Realschule). It begins with a short literary review about the application of graphic novels in language learning and then continues with a description of an intervention in a secondary school in Germany. The article describes how the learners are introduced to the graphic novel as a multimodal medium and describes the different tasks and their relevance in the development of multi-literacies. The aim of the teaching sequence was to involve learners in meaningful communicative activities which cater to their needs and which ensure a development of all skills as well as their general competencies regarding the use of sequential art. Whether this aim was accomplished will also be reflected on.